Waffles “Artek” in Russian Cultural Texts - Ermashova, Irina (Poznańskie Studia Slawistyczne, 2024)
In this article, the function of the brand name “Artek waffles” in Russian-language texts such as poetry, prose, and songs will be presented. For many years, the product name has been associated with the “Artek myth,” the sea and childhood, which has found confirmation in artistic texts. It is worth considering what meanings does the brand name encode today?